PRAKTIK PENGALAMAN LAPANGAN BERBASIS KOLABORATIF ANTARA MAHASISWA DENGAN GURU PAMONG DI MTsN KABUPATEN GOWA - ., Usman; Hanafy, Muhammad Sain; ., Bahraeni (Inspiratif Pendidikan, 2018)
The practice of collaborative based field experience between students and tutor teachers at MTsN 1 in Gowa Regency is one of the authors’ research results in 2018. This paper is devoted to reviewing the response of students of Islamic Education Department of Tarbiyah and Teacher Training UIN Alauddin Makassar and tutor teachers where they implement collaborative PPL (at MTsN Gowa Regency). The data sources in this study were 18 students (through 3 PPL groups) and 3 tutors. This study describes 3 things: (1) the implementation of Collaborative-based Field Experience Practices between Students and Teachers; (2) student responses to the implementation of collaborative practice based on field experience between tutors and students; and (3) Pamong teacher’s response to the implementation of collaborative practice based on field experience between tutor teachers and students. The results of the study show that: (1) the implementation of Collaborative-based Field Experience Practices between Students and Teachers in Gowa District MTsN has proceeded according to the procedures for implementing activities through stages: (a) registration and selection through faculty academics; (b) student debriefing activities; (c) workshop for tutors and tutors; (d) release and delivery of PPL students; (e) school observation and program planning; (f) teaching guided patterns 75:25; (h) FGD 1; (i) implementation of guided learning pattern 50:50; (j) FGD 2; (k) independent teaching; (l) FGD 3; (m) practice exam; (n) student withdrawal; and (o) preparation of reports; (2) student responses to the implementation of collaborative-based field experience practices are included in the positive category, namely the average value of 2.99 (good); (3) the response of tutor teachers to the implementation of collaborative-based field experience practices is included in the positive category, namely the average value of 3.04 (good).